Anlotinib Reverses Multidrug Resistance (MDR) in Osteosarcoma by Inhibiting P-Glycoprotein (PGP1) Function In Vitro and In Vivo - Wang, Gangyang; Cao, Lingling; Jiang, Yafei; Zhang, Tao; Wang, Hongsheng; Wang, Zhuoying; Xu, Jing; Mao, Min; Hua, Yingqi; Cai, Zhengdong; Ma, Xiaojun; Hu, Shuo; et al. (Frontiers in Pharmacology, 2022)
Overexpression of the multidrug resistance (MDR)-related protein P-glycoprotein (PGP1), which actively extrudes chemotherapeutic agents from cells and significantly decreases the efficacy of chemotherapy, is viewed as a major obstacle in osteosarcoma chemotherapy. Anlotinib, a novel tyrosine kinase inhibitor (TKI), has good anti-tumor effects in a variety of solid tumors. However, there are few studies on the mechanism of anlotinib reversing chemotherapy resistance in osteosarcoma. In this study, cellular assays were performed in vitro and in vivo to evaluate the MDR reversal effects of anlotinib on multidrug-resistant osteosarcoma cell lines. Drug efflux and intracellular drug accumulation were measured by flow cytometry. The vanadate-sensitive ATPase activity of PGP1 was measured in the presence of a range of anlotinib concentrations. The protein expression level of ABCB1 was detected by Western blotting and immunofluorescence analysis. Our results showed that anlotinib significantly increased the sensitivity of KHOSR2 and U2OSR2 cells (which overexpress PGP1) to chemotherapeutic agents in vitro and in a KHOSR2 xenograft nude mouse model in vivo. Mechanistically, anlotinib increases the intracellular accumulation of PGP1 substrates by inhibiting the efflux function of PGP1 in multidrug-resistant cell lines. Furthermore, anlotinib stimulated the ATPase activity of PGP1 but affected neither the protein expression level nor the localization of PGP1. In animal studies, anlotinib in combination with doxorubicin (DOX) significantly decreased the tumor growth rate and the tumor size in the KHOSR2 xenograft nude mouse model. Overall, our findings suggest that anlotinib may be useful for circumventing MDR to other conventional antineoplastic drugs.